Uncommon manifestations of Listeria monocytogenes infection - Chavada, Ruchir (BMC Infect Dis, 2014)
BACKGROUND: Listeria monocytogenes causes gastroenteritis, meningitis and bacteraemia in immunocompromised, pregnant patients, the elderly as well in immunocompetent patients. Focal infections with this organism are uncommon, especially in sporadic (non-outbreak) setting, require high index of suspicion and are challenging to diagnose. We present 3 cases of Listeria monocytogenes presenting as focal infections to our hospitals, all of which are the first reported cases from Australia. CASE PRESENTATION: Three unrelated cases of unique focal infections caused by Listeria monocytogenes are presented. 1) A 73 year old Caucasian lady on immunosuppression for colorectal cancer presented with prosthetic knee joint septic arthritis, 2) An 83 year old Caucasian man presented with prosthetic vascular graft infection and 3) A 60 year old Asian man with perianal abscess. Except for case 1, the other cases had a prolonged duration of symptoms on presentation. Listeria was not thought to be causative organism in any of these cases until microbiological specimens isolated the organism. Matrix Associated Laser Desorption/Ionization-Time of Flight Mass Spectrometry (MALDI-TOF MS) assisted in making an earlier diagnosis of the infection in all three cases. All of these patients had Listeria monocytogenes isolated from clinical specimens. They were managed with antibiotics and surgery with favourable outcomes. Public health investigations to determine any dietary association were done, however no intervention was thought to be necessary in any of the cases except provide dietary advice. The first two cases highlight the importance of microbiological sampling in serious infections for definitive antibiotic therapy to be administered. CONCLUSION: Sporadic focal infections with Listeria occur infrequently and are often not diagnosed till culture results from microbiological specimens become available. Dietary history should be an important aspect of thorough clinical history and food consumption advice is crucial in immunocompromised patients on similar lines as given to pregnant women about listeriosis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12879-014-0641-x) contains supplementary material, which is available to authorized users.